Tungo sa patakarang industriyal ng Pilipinas - Tullao, Tereso S. 4 0 16; 5 (Manila, Philippines : De La Salle University Press, 1993)
Industrial policy in the Philippines.
In Tagalog.
Includes bibliographical references (p. [299]-305) and index.
Keywords: 2 -- 0; 6; Industrial policy -- Philippines. -- 20; 20; 2